EFFICACY OF HEALTH EDUCATION ON ENHANCING IMMUNITY TO REDUCE INFECTION INCIDENCE IN INFANT AND TODDLER POPULATIONS - Harwin Holilah Desyanti; Nandalita Sahro Nikmatul Maula; Ulfa Tri Putri Amelia; Risky Amelia (Jurnal Endurance, 2026)
Infections in infants and toddlers are significant health issues in developing countries, including Indonesia, particularly in rural areas with limited access to healthcare services. This study aims to evaluate the effectiveness of a health education program on immunity in reducing the incidence of infections among infants and toddlers in Sumber Kokap Village, Bondowoso Regency. The research design used is a quasi-experimental approach with a pretest-posttest design involving 56 mothers as respondents. The study results show a significant increase in maternal knowledge about immunity after participating in the health education program, with the average knowledge score rising from 62.3 before the intervention to 78.9 after the intervention. Statistical tests indicate a statistically significant difference (p-value < 0.001) between pre- and post-intervention knowledge, suggesting that the health education provided was effective in enhancing maternal knowledge and awareness regarding the importance of immunity and infection prevention in infants and toddlers. These findings underscore the importance of health education programs in improving child health in rural areas and provide a scientific basis for broader health policy development in Indonesia.